Association Between Interorganizational Collaboration in Opioid Response and Treatment Capacity for Opioid Use Disorder in Counties of Five States: A Cross-Sectional Study. (July 2022) - Swann, William L; DiNardi, Michael; Schreiber, Terri L
Background: Local governments on the front lines of the opioid epidemic often collaborate across organizations to achieve a more comprehensive opioid response. Collaboration is especially important in rural communities, which can lack capacity for addressing health crises, yet little is known about how local collaboration in opioid response relates to key outputs like treatment capacity. Purpose: This cross-sectional study examined the association between local governments' interorganizational collaboration activity and agonist treatment capacity for opioid use disorder (OUD), and whether this association was stronger for rural than for metropolitan communities. Methods: Data on the location of facilities providing buprenorphine and methadone were merged with a 2019 survey of all 358 counties in 5 states (CO, NC, OH, PA, and WA) that inquired about their collaboration activity for opioid response. Regression analysis was used to estimate the effect of a collaboration activity index and its constituent items on the capacity to provide buprenorphine or methadone in a county and whether this differed by urbanicity. Results: A response rate of 47.8% yielded an analytic sample of n = 171 counties, including 77 metropolitan, 50 micropolitan, and 44 rural counties. Controlling for covariates, a 1-unit increase in the collaboration activity index was associated with 0.155 (95% CI = 0.005, 0.304) more methadone facilities, ie, opioid treatment programs (OTPs), per 100 000 population. An interaction model indicated this association was stronger for rural (average marginal effect = 0.354, 95% CI = 0.110, 0.599) than for non-rural counties. Separate models revealed intergovernmental data and information sharing, formal agreements, and organizational reforms were driving the above associations. Collaboration activity did not vary with the capacity to provide buprenorphine at non-OTP facilities. Spatial models used to account for spatial dependence occurring with OUD treatment capacity showed similar results. Conclusion: Rural communities may be able to leverage collaborations in opioid response to expand treatment capacity through OTPs.